Investigation of liquid water heterogeneities in large area proton exchange membrane fuel cells using a Darcy two-phase flow model in a multiphysics code. (15th November 2022) - Tardy, Erwan; Poirot-Crouvezier, Jean-Philippe; Schott, Pascal; Morel, Christophe; Serre, Guillaume; Bultel, Yann
Abstract: Proper management of the liquid water and heat produced in proton exchange membrane (PEM) fuel cells remains crucial to increase both its performance and durability. In this study, a two-phase flow and multicomponent model, called two-fluid model, is developed in the commercial COMSOL Multiphysics® software to investigate the liquid water heterogeneities in large area PEM fuel cells, considering the real flow fields in the bipolar plate. A macroscopic pseudo-3D multi-layers approach has been chosen and generalized Darcy's relation is used both in the membrane-electrode assembly (MEA) and in the channel. The model considers two-phase flow and gas convection and diffusion coupled with electrochemistry and water transport through the membrane. The numerical results are compared to one-fluid model results and liquid water measurements obtained by neutron imaging for several operating conditions. Finally, according to the good agreement between the two-fluid and experimentation results, the numerical water distribution is examined in each component of the cell, exhibiting very heterogeneous water thickness over the cell surface. Graphical abstract: Image 1 Highlights: Darcy two-phase flow model compared with neutron imaging measurements. Liquid water distribution in each layer of the cell. Good agreement of the two-phase flow model for high power condition. Impact of the flow fields design on liquid water thickness distribution.